The Role of Taxes and BUMD Profitability in Driving Local Revenue - Tajuddin, Imran; Andi Muhammad Fara Kessi (Paradoks : Jurnal Ilmu Ekonomi, 2025)
This study sets out to explore how two important financial factors—local taxes and the profits from Regional Owned Enterprises (BUMD)—contribute to the increase of Regional Original Revenue (PAD) in Gowa Regency. More specifically, it aims to answer two main questions: (1) how local tax collection affects Gowa’s PAD, and (2) how the profitability of BUMDs influences the region’s own-source revenue. To answer these questions, the research uses a quantitative approach, relying on numerical data to identify patterns and relationships. The data used in this study comes from official publications by the Central Statistics Agency (BPS) and the Regional Revenue Agency of Gowa Regency, covering the years 2010 to 2020. For the analysis, a multiple regression method is applied. This technique helps determine the extent to which each variable—local taxes and BUMD profits—affects PAD, both individually and together. It provides a clearer picture of which factor plays a bigger role and how they work in tandem to influence regional revenue. By understanding these dynamics, the study hopes to offer practical insights for local government decision-makers, especially in designing strategies to boost financial self-reliance and strengthen the economic foundation of Gowa Regency.